Interactive nutrition education for pregnant women: Strengthening maternal health and environmental sustainability in stunting prevention - Sanas, Nurhidayah Tiasya; Resky, Shulystiawaty Desy (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Pregnancy is a critical period that determines both maternal and child health while influencing household food choices and environmental sustainability. Limited nutrition literacy during pregnancy not only increases the risk of malnutrition and stunting but also perpetuates unsustainable dietary practices that burden local ecosystems. This study aims to optimise pregnant women’s nutrition understanding through interactive education programmes that strengthen maternal health and promote environmentally sustainable practices. By emphasising balanced nutrition, positive attitudes, and the use of local food resources, the programme seeks to prevent stunting while reducing ecological impact. Method: A quasi-experimental pre-test and post-test design was employed with 50 pregnant women selected through purposive sampling. The intervention consisted of animated educational videos, interactive simulations on sustainable food choices, quiz-based learning, and guided group discussions with health workers. Findings: Findings demonstrated a significant improvement in nutrition knowledge among the intervention group compared to the control group (Δ = 2.96 vs 0.4; p < 0.001). Beyond knowledge, participants reported greater awareness of the benefits of local, environmentally friendly food consumption patterns as part of stunting prevention efforts. Conclusion: Interactive education effectively enhances maternal nutritional literacy while integrating environmental sustainability into dietary behaviour. This dual benefit highlights the potential of participatory, eco-conscious educational models to improve maternal and child health outcomes while fostering sustainable food systems at the community level. Future researchers can compare various other education methods, such as digital-based education or a combination of conventional and interactive education, to determine the most effective approach in increasing mothers' knowledge and behavioural change in stunting prevention. Novelty/Originality of this article: This study uniquely integrates maternal nutrition education with environmental sustainability, using interactive, eco-conscious methods to simultaneously prevent stunting and promote sustainable dietary practices.